Comparison and Review of the Advantages of the Fractal Method (Variogram) With Respect to the Nettelton in Determining the Density of the Bouguer Plane in the Southern Hormozgan: Iran - Reza, Samadi Hamid; Asghar, Teymoorian (International Journal of Geography and Geology, 2013)
In this paper we describe a comparison between the methods of Variogram and Nettelton to establish the density of the Bouguer plane. The Nettelton’s method is a common method for determining the density along a profile which is based on the least chosen profile’s topographic resemblance with the chosen density of related to that profile of the region. The variogram method based on fractal geometry. This method is based on minimizing surface roughness of bouguer anomaly. The fractal dimension of surface has been used as surface roughness of bouguer anomaly. Using this method, the optimal density of Charak area in south of Hormozgan province can be determined which is 2/7 g/cm3forthe under-research area. The density of the Bouguer plane in the region by the Nettelton’s method has been calculated 2/3g/cm3. This determined optimal density has been used in correcting and reviewing its result in the case of Isostazy state and some very good results have been achieved which has an amazing coincidence with the regional geology and the drilled exploration wells in the area.